Natural Products in Drug discovery: Current Trends - Nathsharma, Santosh Kumar (AG Volumes, 2025)
Medical chemicals have been found in nature for thousands of years, and a staggering number of modern medicines have been shown to have natural roots. For many years, people have employed plants as herbal remedies to cure a variety of illnesses, and the numerous natural compounds they produce have served as inspiration for the creation of new medications. This demand will be met in large part by natural goods via the ongoing investigation of the world's biodiversity, much of which is yet unknown. In this article review the various literature’s study on “natural products in drug discovery”. In conclusion, natural products have been a fundamental component of drug discovery for an extended period, providing useful lead compounds for the development of new therapeutics. Advances in technology have enhanced the selection, identification, and optimization of plant-derived phytochemicals, improving their efficacy and safety. Despite challenges in natural product development, innovative strategies continue to drive drug discovery, addressing both communicable and non-communicable diseases. Plant-based biologics have been further emphasised as a potential vaccine development strategy during the COVID-19 pandemic. In areas such as "immunosuppression, anti-infectives, and metabolic disorders", natural products continue to be a critical source of innovative treatments, as a result of the renewed interest in them as a result of the constraints of alternative drug discovery methodologies.